A review on medicinal properties of Nigella sativa Linn and its role in opioid addiction - Nasir, Mohamad; Liyana Hazwani, Mohd Adnan; Khairi, Che Mat; Rohayah, Husain; Nor Hidayah, Abu Bakar; Mohd Shahril, Othman; Syed Hadzrullathfi, Syed Omar; Khamsah Suryati, Mohd (2015)
Nigella sativa or Habbatus sauda' has many therapeutic properties especially in medicinal worlds. The herb possesses many important active compounds such as thymoquinone and high in nutritional values. Because of this, it has been used to cure many illnesses in addition of a hadith from Hazrat Muhammad (PBUH) that. 'black seed is treatment of every disease but death [AI-Bukhaari and Muslim]. Hence, this mini review article is trying to briefly discuss about several aspects of medicinal properties. calcium channel blocker, chemical compositions and characteristics of Nigella sativa from the literatures.